THE EVOLUTION OF THE STATE FAMILY POLICY IN EUROPEAN COUNTRIES: CHANGING PROBLEMS, PRIORITIES AND PRACTICES - A. V. Noskova (Vestnik MGIMO-Universiteta)
The paper describes some common peculiarities in evolution of the State family politics and policies in Europe since the middle of the XIX century to our days. Неге we define the family policy widely enough as the state activity (ideological, legislative, economic, social) concerning a family. The State family policy has four main dimensions such as demographical, social, gender and existential ones. The analysis of the long-term trends in European family policies made it possible to draw four main periods in its evolution. A set of the main problems, priorities and practices is defined for each period. The article also presents the links between the origin of every new period and the changing families, demographical and social realities. The first period (from the second half of the XIX century till the end of the 1940th) is described as the institutionalization of the European family policy. The main problem of this period is the demographic one. The links between the institutionalization of the European family policy and the changes in family life, demographic and social changes in the boundary of the XIX-XX centuries are shown. The second period (the 1950th) is characterized by the development of the social dimension as a part of the becoming European welfare state. In 1950-s, the main focus in family policies was made on the overcoming of the family poverty. The third period (the 1960th – the end of the 1980th) is characterized by a pluralization of the problems, strategies, measures of family policy under the influence of the differentiation of family structures and styles of family life. The fourth period (from the beginning of the 1990th to the present time) deals with reformatting of the conventional relations of the state and a family in the conditions of a new family, demographic, social and economic European context. The article presents the diversity of the family policy models in the European countries in their connection with the political and ideological factors. Special attention is paid to interdisciplinary scientific family studies which are directed to the practical solution of the modern family problems. It is noted that the European scientific centers for family studies and researches play a significant role in the scientific maintenance of European family policy.